Pertanggungjawaban Hukum Terhadap Pembuang Limbah Yang Melewati Baku Mutu - Marliawati, Sari; Ardiansah; Kadaryanto, Bagio (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2022)
Pollution is a concern in Pelalawan Regency due to waste from various industries or factories that operate. This article attempts to clarify the legal responsibility for waste disposal that exceeds environmental quality standards, define the issues that impede it, and explain what efforts may be taken in accordance with Law No. 32 of 2009 on Environmental Protection and Management. This study opts for a sort of sociological legal research that includes a number of people who are knowledgeable on the subject. According to the findings of the investigation, legal responsibility for waste disposal that exceeded quality criteria in Pelalawan Regency had not been adequately performed out. The company's lack of current and environmentally acceptable waste treatment equipment was discovered to be an impediment. Furthermore, there is still a lack of personnel from connected agencies, a restricted number of operational vehicles in monitoring operations, and an appropriate laboratory to make waste sample examination simpler